Perceptions of active learning among Faculty of Business students / Aishah Musa...[et al.] - Musa, Aishah; Ismail, Junaida; Abdul Jalil, Muna; Bidin, Samsiah; Ali, Siti Meriam (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
One of the criteria for student’s success in learning is student engagement. Active Learning is one platform to enhance student engagement. However, active learning is rarely used as a learning tools at the tertiary level. According to the National Survey of student Engagement (NSSE) and the Australian survey of students Engagement (AUSSE), active learning involves “students’ efforts to actively construct their knowledge”. Active learning is defined as activities that students do to construct knowledge and understanding. Thus, to venture into the issues of active learning this study is constructed to determine the students’ perceptions of active learning. The students were given a set of survey to rate their perceptions towards active learning approach that was being applied by their respective lecturer. Their ratings were gathered and analysed using SPSS Software. In total there were 166 respondents from Faculty Business Management of UiTM Kedah. Majority of the respondents were female with 118 students. The findings revealed that majority of respondents preferred active learning as it helped them to remember things better, enjoyed the lesson and improved their social skills. It is hoped that this study will provide good understandings to lecturers in terms of promoting their creativity in teaching especially in applying active learning approach.